2021
DOI: 10.3390/eng2030019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electric Power Generation Growth in Pakistan: Falling into the Vicious Cycle of Coal

Abstract: This paper aims to analyze national policies of Pakistan taking into account the complexity of electric power generation, growth, and complying with multilateral agreements. Systems thinking has been applied to understand the complexity of energy scenario of Pakistan by representing it with a causal loop diagram (CLD) which displays the interconnectedness and feedbacks of the system. Analysis is based on systems archetypes to diagnose the system behavior, i.e., falling into the vicious cycle of coal. A stock-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Therefore, the demand for energy remains higher in this sector. Similarly, the study of Durrani, Khan, and Ahmad (2021) specified that energy is an important element for economic growth as part of the productive process. Moreover, energy is inseparable from the production process of industries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the demand for energy remains higher in this sector. Similarly, the study of Durrani, Khan, and Ahmad (2021) specified that energy is an important element for economic growth as part of the productive process. Moreover, energy is inseparable from the production process of industries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Khan (2015) stated that medium to long-term gas demand in Pakistan depends on a single equation demand model where per-capital demand has a direct relation with real income, real prices, and real prices of a substitute. Correspondingly, Durrani, Khan, and Ahmad (2021) found that a high population growth rate, industrialization, rural gasification, and urbanization increase the demand for energy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations